Marmoset cytochrome P450 4A11, a novel arachidonic acid and lauric acid ω-hydroxylase expressed in liver and kidney tissues. (3rd July 2017) - Uehara, Shotaro; Uno, Yasuhiro; Ishii, Sakura; Inoue, Takashi; Sasaki, Erika; Yamazaki, Hiroshi
Abstract: 1. A cDNA encoding novel cytochrome P450 (P450) 4A enzyme was cloned from marmoset livers by reverse transcription (RT)-polymerase chain reaction (PCR) based on the marmoset genome sequences. The amino acid sequence deduced from P450 4A11 cDNA contained consensus sequences of six substrate recognition sites and one heme-binding domain. 2. Marmoset P450 4A11, highly identical (85–88%) to cynomolgus monkey and human P450 4A enzymes, was grouped into the same cluster as cynomolgus monkey and human P450 4A enzymes by phylogenetic analysis. 3. The tissue distribution analyses by real-time RT PCR and immunoblotting demonstrated that marmoset P450 4A11 mRNA and proteins were expressed in kidneys and livers. Marmoset P450 4A11 enzyme heterologously expressed in Escherichia coli preferentially catalyzed the ω-hydroxylation of arachidonic acid and lauric acid, similar to cynomolgus monkey and human P450 4A11 enzymes. However, lauric acid ω-hydroxylation activity of marmoset P450 4A11 was low compared with those of marmoset liver microsomes. 4. These results indicated that novel marmoset P450 4A11 was also a fatty acid ω-hydroxylase expressed in kidneys and livers, with the same regioselectivity (at ω-position of fatty acid) as cynomolgus monkey and human P450 4A enzymes.